Prices and Productivity in Agriculture - Fulginiti, Lilyan E.; Perrin, Richard K. (The Review of Economics and Statistics, 1993)
Developing countries often tax agriculture heavily, a practice that might affect the productivity as well as the quantity of resources allocated to agriculture. A variable-coefficient, cross-country agricultural production function is estimated, with past price expectations among the determinants of the production coefficients. Productivity's responsiveness to those expectations implies that had these developing economies eliminated price interventions, agricultural productivity would have increased on average by about a fourth. Copyright 1993 by MIT Press.